A Noonan-like short stature syndrome with sparse hair. Issue 2 (April 1986) - Baraitser, M; Patton, M A
Abstract : Noonan's syndrome is a clinically recognisable short stature syndrome with autosomal dominant inheritance. The diagnosis can be difficult as the phenotypic expression is very variable. There has been an attempt to divide this syndrome into type I (in which the facial features, especially ptosis, antimongoloid eye slant, and hypertelorism are prominent) and type II (where cardiological abnormalities are more to the fore), but this has not yet been confirmed by other studies.